PEMANFAATAN BUAH PEDADA (SONNERATIA CASEOLARIS) PADA PEMBUATAN PERMEN JELLY - Pradhistama Rizqi Alharanu; Nova Eviana (Eduturisma, 2020)
Indonesia's mangrove forest area, which covers 23% of the world's total mangrove forests, has great potential as a tourist destination. In addition, mangrove forests with fruit pedada (Sonneratia caseolaris) can also be used as a source of food. The use of pedada as an addictive substance in jelly candy products is one example. This study aims to analyze the making process and products quality of jelly candy with additional ingredients of pedada juice and to test the preferences for jelly candy products with added pedada fruit juice. The hedonic test was carried out on 100 respondents and analyzed using the average test. The results showed that the pedada juice would affect the making process and the quality of the jelly candy product. The higher the pedada juice concentrate, the stronger the effect on taste, aroma, texture, chewiness, and transparency. The hedonic test results showed that the respondents preferred jelly candy products with a lower pedada fruit juice concentrate.